STT3A-mediated mega protein complex assembly during dengue and Zika virus infection - Tao Liu; Natasha W. Hanners; Huangheng Tao; Claudia Szabo; Dao Xu; Wei Lin; John W. Schoggins; Nan Yan; Jianjun Wu (iScience)
Summary: Flavivirus replication in mammalian cells requires host oligosaccharyltransferase (OST) complex, which is classically known to catalyze protein N-glycosylation. However, enzymatic activity of OST is not required for flavivirus infection, leaving the underlying mechanism puzzling. We show the STT3A sub-complex of OST, including STT3A and DC2, to be critically required for dengue virus (DENV) and Zika virus (ZIKV) infection. We find that STT3A nucleates a mega protein complex assembly during DENV infection as a scaffold through its interaction with other OST subunits, translocon proteins, and viral nonstructural proteins. The integrity of this mega protein complex is important for supporting flavivirus infection. We also identified a small-molecule compound NSC-323241 that disrupts STT3A-mediated mega protein complex assembly and potently blocks DENV and ZIKV infection. Together, our study reveals a scaffolding function of STT3A in flavivirus infection through comprehensive molecular dissection of the multi-subunit OST complex and associated host and viral proteins.